Uncovering the intersection of women's empowerment and gender equality for climate adaptive capacities in climate hotspots in Zambia - Kihoro, Esther; Lecoutere, Els; Mishra, Avni (CGIAR GENDER Impact Platform, 2023)
Women in agrifood systems in low- and middle-income countries are more likely than men to be adversely affected by climate change. They also have more limited climate-adaptive capacities due to socioeconomic and cultural factors, such as restricted access to resources, information and technology, discriminatory gender norms, and limited decision-making power. This study examines the extent to which women’s empowerment in the household is associated with intrahousehold gender equality for climate-adaptive capacities and practices in places experiencing significant climate change hazards and stressors. It also explores the strength of the association of different dimensions of women’s empowerment with gender equality in climate-adaptive capacities. The study concentrates on the Luapula and Northwestern provinces in Zambia, where women face high climate change risks. The study uses gender-disaggregated intrahousehold data that captures information about access to, and knowledge and adoption of, practices that support climate-adaptive capacities, women’s empowerment and perceived climate change. This data was collected from 199 households headed by a married or partnered couple, and regression analysis was applied to the data to test two hypotheses. The results support the first hypothesis of a positive correlation between women’s empowerment and intrahousehold gender equality to climate-adaptive capacities and, more specifically, access to technical advice on climate-smart agricultural practices. The results also support the second hypothesis that various dimensions of women’s empowerment—attitudes toward violence (norms), intrinsic agency, instrumental agency and collective agency—are associated with intrahousehold gender equality in climate-adaptive capacities in varying ways. The study’s findings highlight the complexity of the relationships between women’s empowerment and gender equality to climate-adaptive capacities in climate change hotspots, and emphasize the need for context-specific analyses and solutions.